TOURISM AND TERRITORY IN THE BANKS OF LAKE ATITLAN, GUATEMALA - Sánchez-Crispín, Álvaro (2017)
The aim of this paper is to explain the territorial syntaxes of tourism in one of the most emblematic places of Guatemala: Atitlan Lake. Around this body of water, and having a spectacular natural background, ten small settlements are located. All of them are of Mayan origin and their population speaks either kaqchiqel or tz’utujil languages, and have a diverse living culture. These communities are trying to gain access to a niche in a highly competitive tourism market.  To reach our research objective, we first examine the geographical setting of tourism at both national and local levels. We also pinpoint some of the relevant features of the natural protected areas in Guatemala, since Atitlan Lake is inserted in the Reserve of Multiple Use of the Atitlan Lake Basin, and we relate all this to the tourist activity.  Finally, we reveal the major centers of the tourism economy in the lake, and end up with a remark on the apparent non-existent relation between tourism and the presence of the natural protected area.